Response of coffee crop (Coffea arabica L.) in agroecologic transition to diferent soil management - Theodoro, Vanessa Cristina de Almeida; Mendes, Antônio Nazareno Guimarães; Guimarães, Rubens José (Coffee Science - ISSN 1984-3909, 1970)
This work had the objective of evaluate the efficiency of different techniques of the organic and conventional managements in the soil fertility and productivity of coffee plants after the first year of agroecologic transition. The experiment was installed in August/2004 in a coffee plantation located in the municipality of Lavras/MG previously cultivated in a conventional management. The experimental design used was the lattice balanced 4x4 in factorial scheme 3x2x2 with five replications and four more additional treatments. Three sources of organic matter were used (castor bean bran, bovine manure and boiler litter) with or without straw of fermented coffee, and with or without the use of green manuring with [Cajanus cajan (L.) Millsp.], in the line spacing of the coffee crop and pulverization with the biofertilizer “supermagro”. The conventional management had the application of ammonium sulfite and the potassium chloride, and conventional foliar manuring. The organic management maintained an appropriate supply of K in the soil, with highlighting the boiler litter and bovine manure. The most significant benefit of the manuring organic in the soil fertility was to increase the K, S and B availability. The treatments of organic managements showed productivity similar to the conventional, due to the existence of nutrient reserves in the soil. It is emphasized the importance of carrying out further research to monitor the agroecologic transition during the first three years of coffee crop management, time required for its organic certification and possible biological reconstruction of soil fertility.